KONSEP PARTISIPASI MASYARAKAT DIENG DALAM PELAKSANAAN PROGRAM PENGEMBANGAN PARIWISATA - Susilo, Susilo (Kepariwisataan: Jurnal Ilmiah, 2018)
Dieng tourism resources is a unity between natural resources, archeological, and community life. These conditions resulted in nearly all processes of tourism development will affect people's lives, and conversely, any community activities will also affect tourism. In every aspect of tourism development needs to involve the community as part of the development impact and receiver. Dieng community participation in social and cultural activities is one manifestation of ngaruhake norm. Ngaruhake is a social norm that aims to maintain harmony within the community scale, but does not apply to a public scale. Participation is based on a moral obligation to realize the common interests or helping others, not for himself personally. Levels of participation can be divided into three groups, namely mokoki (main actors), ngombyongi (supporting actor), and masabodoa (not involved). Spatially, greater area of space, community participation will be lower and the other hand, narrow region of space will increase community participation. Keywords: Participation, Tourism, Dieng